7.III. Pycnogonida from Jørgen Brønlund Fjord, North Greenland. - Just, Jean (Meddelelser om Grønland, 1970)
From Jørgen Brønlund Fjord , North Greenland are recorded four species of Pycnogonida, viz. Boreonymphon robustum G. O . SARS, Nymphon hirtipes BELL, N . macronyx G. O. SARS, and N . stromi KRÖYER.